Protection of migrant workers in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Eishan Jan, Mohammad Naqib (The Malaysian Current Law Journal Sdn Bhd, 2016)
As human beings, migrant workers deserve to be treated with dignity and respect. The bitter truth, however, is that migrant workers around the world are exploited at the hands of their employers who most likely view them with xenophobic eyes, who mistreat them, deny them minimum labour standards and subject them to human rights violations including forced labour. It is not uncommon to hear inhumane treatment towards these migrant workers, male and female alike. Some of them are abused, deprived of proper accommodation and even food and treated very poorly. A good employer is all the migrant workers need to make their ends meet. A bad employer would spell for him/her ‘hell on earth’. Unfortunately, Malaysia has its fair share of ‘hell on earth’ cases involving migrant workers like the recent case involving an Indian couple. Hence, this article discusses the protection of migrant workers with reference to the law and practice in Malaysia.